2019
DOI: 10.4093/dmj.2018.0052
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Protects Against High Glucose-Induced β-Cell Apoptosis by Attenuating Endoplasmic Reticulum Stress via Inactivation of Cyclin-Dependent Kinase 5

Abstract: Background Chronic hyperglycemia has deleterious effects on pancreatic β-cell function and turnover. Recent studies support the view that cyclin-dependent kinase 5 (CDK5) plays a role in β-cell failure under hyperglycemic conditions. However, little is known about how CDK5 impair β-cell function. Myricetin, a natural flavonoid, has therapeutic potential for the treatment of type 2 diabetes mellitus. In this study, we examined the effect of myricetin on high glucose (HG)-induced β-cell apoptosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…CDK5 has also been demonstrated to play a role in the activity of dopamine-and cAMP-regulated neuronal phosphoprotein 32, which controls dopamine signaling in specific neurons in adult mice [68,86]. Lastly, in addition to the roles for CDK5 previously discussed, CDK5 function has also been implicated in many other cellular processes such as cell cycle control and gene regulation, cell survival and apoptosis, membrane dynamics, focal adhesion formation, intracellular trafficking, and glucose metabolism, overall demonstrating the varied and essential roles of CDK5 in proper cell function [1,33,36,68,69,87,88].…”
Section: Function Of Cdk5 In Neuronal Developmentmentioning
confidence: 91%
See 1 more Smart Citation
“…CDK5 has also been demonstrated to play a role in the activity of dopamine-and cAMP-regulated neuronal phosphoprotein 32, which controls dopamine signaling in specific neurons in adult mice [68,86]. Lastly, in addition to the roles for CDK5 previously discussed, CDK5 function has also been implicated in many other cellular processes such as cell cycle control and gene regulation, cell survival and apoptosis, membrane dynamics, focal adhesion formation, intracellular trafficking, and glucose metabolism, overall demonstrating the varied and essential roles of CDK5 in proper cell function [1,33,36,68,69,87,88].…”
Section: Function Of Cdk5 In Neuronal Developmentmentioning
confidence: 91%
“…CDK5 has also been identified to play important roles in processes such as cell death and proliferation, angiogenesis, migration of epithelial and cancer cells, inflammation, myogenesis, glucose metabolism, and insulin secretion in non-neuronal cells [53,87,[89][90][91][92]. These studies have investigated CDK5 function in cells such as cells of hematopoietic lineage, HEK293, COS7, MEF, HCT116, HeLa, adipoctyes, pancreatic β cells, and many other non-neuronal cell types [53,91].…”
Section: Function Of Cdk5 In Non-neuronal Cellsmentioning
confidence: 99%
“…Myricetin antidiabetic activity has been reported by several authors in the last few years and limited reports are also available on its anti-obesity activity but in this review, we focused on only its antidiabetic potential. Karunakaran et al [101] reported the in vitro effect of myricetin on high glucose-induced β-cell apoptosis, possibly via cyclin-dependent kinase 5 (CDK5) inhibition. Data revealed that myricetin (20 μM) significantly protect β-cells reducing apoptosis in INS-1 cells and rat islets that were incubated with glucose at the concentration of 30 mM for 24 and 48 h, respectively.…”
Section: Antidiabetic Activitiesmentioning
confidence: 99%
“…The oxidative damage model of INS-1 cells was mainly induced by several inducers, such as high glucose [48,49], palmitic acid [50], and hydrogen peroxide [51,52]. In this study, we used H 2 O 2 as an oxidizing agent, which is commonly used to cause irreversible oxidative damage in various cell models [53].…”
Section: Methodsmentioning
confidence: 99%